Lumbar puncture in patients using anticoagulants and antiplatelet agents - Domingues, Renan; Bruniera, Gustavo; Brunale, Fernando; Mangueira, Cristóvão; Senne, Carlos (Arquivos de Neuro-Psiquiatria, 2016)
The use of anticoagulants and antiplatelet agents has largely increased. Diagnostic lumbar puncture in patients taking these drugs represents a challenge considering the opposing risks of bleeding and thrombotic complications. To date there are no controlled trials, specific guidelines, nor clear recommendations in this area. In the present review we make some recommendations about lumbar puncture in patients using these drugs. Our recommendations take into consideration the pharmacology of these drugs, the thrombotic risk according to the underlying disease, and the urgency in cerebrospinal fluid analysis. Evaluating such information and a rigorous monitoring of neurological symptoms after lumbar puncture are crucial to minimize the risk of hemorrhage associated neurological deficits. An individualized patient decision-making and an effective communication between the assistant physician and the responsible for conducting the lumbar puncture are essential to minimize potential risks.
Keywords: anticoagulants; platelet aggregation inhibitors; spinal puncture; hematoma, spinal